Diketopyrrolopyrrole Bis‐Phosphonate Conjugate: A New Fluorescent Probe for In Vitro Bone Imaging. Issue 14 (12th February 2019) - Chiminazzo, Andrea; Borsato, Giuseppe; Favero, Alessia; Fabbro, Chiara; McKenna, Charles E.; Dalle Carbonare, Luca Giuseppe; Valenti, Maria Teresa; Fabris, Fabrizio; Scarso, Alessandro
Abstract: The synthesis of a conjugate molecule between an unusual red‐fluorescent diketopyrrolopyrrole (DPP) unit and a bis‐phosphonate (BP) precursor by a click‐chemistry strategy to target bone tissue and monitor the interaction is reported. After thorough investigation, conjugation through a triazole unit between a γ‐azido rather than a β‐azido BP and an alkyne‐functionalized DPP fluorophore group turned out to be the winning strategy. Visualization of the DPP‐BP conjugate on osteoclasts and specific antiresorption activity were successfully demonstrated. Abstract : To the bone : The conjugate of a red‐fluorescent diketopyrrolopyrrole (DPP) unit and a bis‐phosphonate (BP) precursor was synthesized by a click‐chemistry strategy as a fluorescent probe targeting bone tissue. Conjugation through a triazole unit between a γ‐azido rather than β‐azido BP and an alkyne‐functionalized DPP fluorophore group turned out to be the successful strategy. Visualization of the DPP‐BP conjugate on osteoclasts and specific antiresorption activity were demonstrated.